An Analysis of Figurative Language Used in Selected Song Lyrics of Taylor Swift in 1989 Album - Fani Auliani; Kismullah Kismullah; Burhansyah Burhansyah (Research in English and Education Journal, 2023)
Figurative Language is considered as one aspect of what gives texts, in particular poetic texts, a special aesthetic value. The study aims to find out figurative language used in songs in the 1989 album by Taylor Swift, and analyze the meaning of figurative language found in 1989 album. The data analyzed is Taylor Swift's selected songs in the 1989 album, namely I Wish You Would, Clean, I Know Place, Out of The Wood, How You Get The Girl, All You Had to Do was Stay, This Love. The research design used is descriptive with a qualitative approach. to analyze the data using the theory of Perrine (1997) related to types of figurative language. The result of the study showed that there are some types of figurative language used in the selected songs in the 1989 album by Taylor Swift, i,e. metaphor, simile, hyperbole, personification, and paradox. From the analysis that has been done, 45 occurencess of figurative language were found in the seven songs. Metaphor consists of 27 occurences, hyperbole consists of 7 occurences, and simile, personification, and paradox consists of 2 occurences, and others figurative language consists of 4 occurences. Therefore, The result shows that the most figurative language found in selected song in the 1989 album by Taylor Swift is metaphor. This thesis can be useful for futher researchers, who are interested in conducting research on figurative language analysis.